Model Pembelajaran Contextual Teaching And Learning (CTL) Berbantu Media Miniatur Lingkungan Untuk Meningkatkan Hasil Belajar IPS - Sulfemi, Wahyu Bagja (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2019)
Classroom Action Research (CAR) was carried out on students in class III Pancoranmas 5 Elementary School Depok as many as 30 students consisting of 17 men and 13 women. This study aims to improve learning outcomes of the Social Sciences Subject using media-assisted contextual teaching and learning (CTL) learning models. Media Miniature Natural and Artificial Environment. In pre-cycle learning, the average grade 49 was obtained, which was completed by 8 people or 26.67%, observations of teachers who had the courage and were able to answer the teacher's questions for only 5 students or 16.67%. rose to 68, the complete number of students was 16 or 53.33%, the observations of teachers who were able to answer the teacher's questions correctly reached 16 or 53.33%. Activity Cycle 2, the average grade gain rose significantly to 94, which was completed as much as 28 or 93.34%. The observations of teachers who have the courage and are able to answer the teacher's questions correctly are 29 or 96.67%. The use of media-assisted Contextual Teaching and Learning (CTL) models The Natural and Artificial Environment Miniature provides a real experience, high-level thinking, learner-centered, critical and creative, meaningful knowledge in life, close to real life, changes in behavior and knowledge. In addition, student learning outcomes can increase.